Isoprenoids from the sponge Gellius varius living in Vietnamese sea - Cuong, Nguyen Xuan; Dang, Nguyen Hai; Thung, Do Cong; Huong, Tran Thu; Kim Thuy, Nguyen Thi; Kiem, Phan Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2014)
Five isoprenoids, cholest-7-ene-3β,5α,6β-triol (1), 6β-methoxycholest-7-ene-3β,5α-diol (2), 5,8-epidioxycholest-6-en-3-ol (3), cholesterol (4) and trans-phytol (5) were isolated from chloroform extract of the sponge Gellius varius collected in Vietnam. Their structures were determined on the basis of the physicochemical and spectroscopic data. This is the first report of compounds 1, 2 and 3 from this species. Keywords: Gellius varius, cholest-7-ene-3β,5α,6β-triol, 6β-methoxycholest-7-ene-3β,5α-diol.